A microfluidic platform for quantitative measurements of effective protein charges and single ion binding in solution1. Issue 18 (14th May 2015) - Herling, Therese W.; Arosio, Paolo; Müller, Thomas; Linse, Sara; Knowles, Tuomas P. J.
<x xml:space="preserve">Abstract</x> Microfluidic electrophoresis enables the comparison of dry sequence and solvated protein charges, and the detection of protein–ion binding.